2010
DOI: 10.1158/1541-7786.mcr-09-0259
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Expression of Stromal-Derived Factor-1 Receptors: CXCR4 and CXCR7 in Human Rhabdomyosarcomas

Abstract: Rhabdomyosarcomas (RMS) express CXCR4 and CXCR7 receptors that bind prometastatic α-chemokine stromal-derived factor-1 (SDF-1). In this report, we analyzed the activity of both promoters in a model of less metastatic human embryonal-RMS cell line (RD) and more metastatic alveolar-like RMS (RD cells transduced with paired box gene 3/forkhead homologue; PAX3-FKHR fusion gene). First, CXCR4 is barely detectable in RD and becomes upregulated in RD/PAX3-FKHR cells. In contrast, CXCR7 highly expressed in RD becomes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 37 publications
4
58
0
Order By: Relevance
“…NF-B is a transcription factor with multiple target genes, so the question arises, which are the genes downstream of FAT10 and NF-B? The microarray expression analysis of FAT10 overexpressing NeHepLxHT and HCT116 cells by Gao et al (2014) revealed that the chemokine receptors CXCR4 and CXCR7 were highly up-regulated in FAT10 overexpressing NeHepLxHT cells, consistent with other data showing that NF-B is a transcription factor for both genes (Katoh and Katoh, 2010;Tarnowski et al, 2010). CXCR4 and −7 are both described to promote invasion and tumor growth in several cancer types (Gao et al, 2010;Heinrich et al, 2012;Liang et al, 2005;Zheng et al, 2010).…”
Section: What Are the Mechanisms Behind Fat10 Overexpression?supporting
confidence: 68%
“…NF-B is a transcription factor with multiple target genes, so the question arises, which are the genes downstream of FAT10 and NF-B? The microarray expression analysis of FAT10 overexpressing NeHepLxHT and HCT116 cells by Gao et al (2014) revealed that the chemokine receptors CXCR4 and CXCR7 were highly up-regulated in FAT10 overexpressing NeHepLxHT cells, consistent with other data showing that NF-B is a transcription factor for both genes (Katoh and Katoh, 2010;Tarnowski et al, 2010). CXCR4 and −7 are both described to promote invasion and tumor growth in several cancer types (Gao et al, 2010;Heinrich et al, 2012;Liang et al, 2005;Zheng et al, 2010).…”
Section: What Are the Mechanisms Behind Fat10 Overexpression?supporting
confidence: 68%
“…Finally, we sought to confirm whether changes in CXCR4 expression influence GBC progression by CXCL12 using GBC cell clones with stable knockdown of CXCR4 because several recent reports indicate that CXCL12 also binds to another 7-transmembrane span receptor called CXCR7 (38,39). Indeed, with CXCR7 identified as a new receptor for CXCL12, the role of the CXCL12/CXCR4 axis in regulating biologic processes in cancer development and progression has become more complex (40).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we returned to a review of the transcriptional regulation of CXCR4, based on the structure of its promoter region (22). As no gene encoding a transcriptional factor that regulates CXCR4 exhibited a change in expression ( Supplementary Fig.…”
Section: Role Of Spheroid Formation On Cxcr4 Expression Involvement mentioning
confidence: 99%